O corpo em-cena : a sociedade administrada e o trauma nas Body modifications - Rodrigues, Alexandra Arnold (2011)
This dissertation had as object of study the phenomenon of Body Modifications. The goal was identify and understand the contemporary cultural injunctions that impregnate the body in Western society and culminate in its hyper-investiment sensory and aesthetic. Also it aimed to uncover the motivations psychic that guarantee compliance of individuals to such practices. For this, it was proposed a dialogue between Critical Theory and Psychoanalysis in elaboration of the research literature. The material to analysis is derived from sites like the "www.bmezine.com": reports and interviews with fans; images, videos and space buying and advertising (www.bmeshop.com). At first, talk about Body Modifications is talk about a suffered looking for which is abject, for a broken body in its biological functions, psychic and social; is talk of bodies multiladed, etymologically, mangled body that suffers decreases. Historically, practices of body modification have been used to undermine grudgingly the autonomy of individuals in processes of torture, or, it corresponded with rites of passage and it ensured a social membership in Indian tribes or necessary in some cultures Orientals. However, it with its integration-assimilation into contemporary western culture, these practices are fetishized and naturalized by totalizing discourses own of market: Indeed, it doesn't correspond more the search for a specific identity cultural and nor a collective historical record. It matches with alienated reproductions of millenarian practices. They are stereotyped practices which lashed with a compromised due, because instrumental, calculate and metrical the territory of body in favor of the effectiveness of technical and scientific apparatus that sustain them. The way that the promise of emancipatory reason falls in instrumentality and a new myth predominates: the domain of merchandise over the body- man backsliding on minority Kantian and in the semi-formation. Despite numerous new the bodies are, as ever, wrapped in a mythical golden, as ponder Adorno and Horkheimer (1947), "the body is taboo, the subject of attraction and repulsion - foundation for the domination of men. However, this does not happen without interfering in the economy libidinal of individuals. Both the skin and pain are structural elements of the psyche human, but the excess current that butchering the senses announces fragilization in instance of ego. Would exist today, this corrupted skin (constant and omnipotent) by body modifications and in the rip of individual and collective memory (which the materiality body appears as the last hope of salvation), a fault in the protective narcissistic function of individuals. Therefore, they would be more vulnerable to state trauma 'arranged' by the managed society. The current passion for real, presented by Zizek, has as subjective correlate a "unfusion pulsion": pulsion of death seated in a deadly masochism, which is expressed in compulsive repetition of practices as the Body Modifications. So we see a manic denial of life drives (self- conservation and sexuality), for example, the stitching holes and castration. Tension with an immanent critique the glamorous printed in thismortification body (Körper) can be the first step towards (re) conquer the living body (Leib).